Acetaminophen-induced cellulitis-like fixed drug eruption - Neila Fathallah; Chaker Ben Salem; Raoudha Slim; Lobna Boussofara; Najet Ghariani; Kamel Bouraoui (Wolters Kluwer Medknow Publications, 2011)
Acetaminophen is a widely used analgesic drug. Its adverse reactions are rare but severe. An 89-year-old man developed an indurated edematous and erythematous plaque on his left arm 1 day after acetaminophen ingestion. Cellulitis was suspected and antibiotictherapy was started but there was no improvement of the rash; there was a spectacular extension of the lesion with occurrence of flaccid vesicles and blisters in the affected sites. The diagnosis of generalized-bullous-fixed drug eruption induced by acetaminophen was considered especially with a reported history of a previous milder reaction occurring in the same site. Acetaminophen was withdrawn and the rash improved significantly. According to the Naranjo probability scale, the eruption experienced by the patient was probably due to acetaminophen. Clinicians should be aware of the ability of acetaminophen to induce fixed drug eruption that may clinically take several aspects and may be misdiagnosed.